The EFFECT OF TOBACCO CIGARETTES ON RATS` ORAL MICROBIOTA - Popova, Tatyana Mikhailovna (Medicinski časopis, 2023)
Objective. The tobacco usage is a risk factor of the variety oral diseases. To date, the effect of this risk factor on the composition of the oral microbial community has been considered by single studies with unclear pathogenetical links. One is possible factor which could be critical is transformation of biocenosis of oral cavity under influence of smoking, so the purpose of the present study was to evaluate the microflora of rats exposed to tobacco cigarette smoke. Methods. We compared the composition of the oral microflora of 20 WAG rats were exposed to smoke of tobacco cigarette and 10 control rats using a culture-based methods targeted at microbial taxonomic and functional profile. Results. At the experiment 60th day, comparative analysis of the microbiota showed that microbiological composition varied considerably between the two groups. In the rats influenced by cigarette smoke, exposure time-related reductions in commensal microflora were noted. At the end of the experiment, the commensal bacteria were markedly reduced. In contrast, the opportunistic bacterial diversity was increased and represented by Gram-negative microorganisms as the major phyla that were introduced: Enterobacter aerogenes, Enterobacter cloacae, Klebsiella pneumoniae, Moraxella catarrhalis, Candida albicans and Escherichia coli, likely because they took advantage of the empty niches created by the cigarette tobacco smoke exposure. Conclusion. We conclude that alterations in the composition, diversity, and function of the oral microbiome occur in association with tobacco smoke components and exposition term. The established risk factors for oral dysbiosis, especially after long-term exposure may contribute to disease development of the oral cavity.